2014
DOI: 10.1056/nejmoa1311989
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urinary Sodium and Potassium Excretion with Blood Pressure

Abstract: In this study, the association of estimated intake of sodium and potassium, as determined from measurements of excretion of these cations, with blood pressure was nonlinear and was most pronounced in persons consuming high-sodium diets, persons with hypertension, and older persons. (Funded by the Heart and Stroke Foundation of Ontario and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
586
13
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 712 publications
(669 citation statements)
references
References 25 publications
39
586
13
13
Order By: Relevance
“…High urinary potassium excretion is reported to be associated with low BP (22,23). In this study, the higher quartile subgroups showed lower Table 3.…”
Section: Discussionsupporting
confidence: 47%
“…High urinary potassium excretion is reported to be associated with low BP (22,23). In this study, the higher quartile subgroups showed lower Table 3.…”
Section: Discussionsupporting
confidence: 47%
“…It is well recognized that higher levels of sodium intake are associated with elevated blood pressure (1)(2)(3). Importantly, the effect of dietary sodium on blood pressure is dependent on other components of the diet and, specifically, its potassium content (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Mendelian forms of hypertension has demonstrated the key role of increased renal salt reabsorption in disease pathogenesis (1)(2)(3)(4). Observational and intervention trials (5,6) also indicate that increased dietary K + lowers blood pressure; however, the mechanism of this effect has been unclear.…”
mentioning
confidence: 99%